Knowledge factors associated with the uptake of improved hygiene and sanitation facilities among households in Kuresoi South Sub-County, Nakuru County, Kenya - Josephine Kithinji; David Masinde; Dickens Omondi Aduda; Kenneth Kipngeno Tonui (International Journal Of Community Medicine And Public Health, 2026)
Background: Access to improved hygiene and sanitation facilities remains a major public health challenge in many rural communities, contributing to persistent burden of preventable infectious diseases. Knowledge of hygiene and sanitation practices is considered an important determinant of household adoption of improved facilities. This study assessed knowledge-related factors associated with the uptake of improved hygiene and sanitation facilities among households in Kuresoi South Sub-County, Nakuru County, Kenya. Methods: A descriptive cross-sectional study using a mixed-methods approach was conducted among 346 households selected through stratified and systematic random sampling. Data were collected using structured questionnaires, observation checklists, and focus group discussions. Quantitative data were analyzed using descriptive statistics, chi-square tests, and binary logistic regression at a 95% confidence level. Qualitative data were analyzed thematically. Results: Overall, 61.3% of households had poor uptake of improved hygiene and sanitation facilities. Chi-square analysis showed significant associations between uptake and knowledge of diseases caused by poor hygiene (χ2=9.849, p=0.007) and knowledge of critical handwashing times (χ2=21.877, p